Lewis Acid and Base Catalysis of YNbO4 Toward Aqueous‐Phase Conversion of Hexose and Triose Sugars to Lactic Acid in Water. Issue 1 (29th October 2019) - Kim, Minjune; Ronchetti, Silvia; Onida, Barbara; Ichikuni, Nobuyuki; Fukuoka, Atsushi; Kato, Hideki; Nakajima, Kiyotaka
Abstract: Amphoteric YNbO4 was synthesized by the simple coprecipitation using (NH4 )3 [Nb(O2 )4 ] and Y(NO3 )3, and examined as a new solid acid‐base bifunctional catalyst for various reactions including aqueous‐phase conversion of glucose to lactic acid. After drying the white precipitate at 353 K for 3 h, the resultant oxide is an amorphous YNbO4 with high densities of Lewis acid sites (0.18 mmol g −1 ) and base sites (0.38 mmol g −1 ). Negatively‐charged lattice oxygen of amorphous YNbO4 functioned as Lewis base sites that promote a Claisen‐Schmidt‐type condensation reaction with acetylacetone and benzaldehyde with comparable activity to reference catalysts. Amorphous YNbO4 can also be applicable to the production of lactic acid from glucose in water, which gives relatively high yields (19.6 %) compared with other reference catalysts. Mechanistic studies using glucose‐1‐ d and 2 H nuclear magnetic resonance spectroscopy (NMR) revealed that YNbO4 first converts glucose to two carbohydrates (glyceraldehyde and pyruvaldehyde) through dehydration via the formation of 3‐deoxyglucosone and subsequent retro‐aldolization, and these intermediates are then converted to lactic acid by both dehydration and isomerization through hydride transfer. Abstract : Sugars conversion : Amorphous YNbO4 combined promising Lewis acidity derived from unsaturated coordination Nb species and Lewis basicity due to localized negative charge of yttrium‐oxygen bond, and facilitated lactic acid formation from glucose in water.